INFLUENCE OF BRAND IMAGE, BRAND TRUST AND PERCEIVED PRODUCT QUALITY ON THE DECISION OF PURCHASING - Rokhmad Budiyono; Arini Novandalina; idyah Yuli Ernawati (JURNAL STIE SEMARANG, 2022)
This study aims to analyze the influence of brand image, brand trust, and perceptions of product quality on purchasing decisions for refill bulgari extreme sport perfume. This research method uses a type of quantitative research, purposive sampling research sample which amounted to 96 people. Data analysis using multiple linear regression. (1) H1 = H0, (2) H2 = H2 + H0, (3) H3 = H0. Significant F test (0.00 <0.05) means that it is declared feasible because the independent variable has a positive and significant effect on the dependent. The determination coefficient (R2) is 041,2 or 41.2%. 41.2% of purchasing decisions are influenced by brand image, brand trust and perceived quality. The conclusion of this study is brand image, brand trust and perceived quality have a significant influence on the sale of perfume products. Results the research use for market improvment bulgari extreme in Indonesia.